The Physical Geography of Georgia - Bolashvili, Nana.; Neidze, Vazha (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is one of the first books in English to give a comprehensive and detailed overview of the complete physical geography of Georgia. It discusses natural and environmental conditions, geology, hydrology, geomorphology, landscapes, and resources and elaborates issues of environmental protection, natural hazards, resource potentials, tourism and many other topics of this multifaceted country. This volume will appeal to researchers, educators and students in the fields of natural and environmental sciences, geography, geology, regional studies and related areas.
1. Location, Territory, Boundaries -- 2. Geology -- 3. Hydrogeology and Mineral Waters -- 4. Mineral Resources -- 5. Relief -- 6. Karst -- 7. Natural Disasters (mudflow, landslide, ets.) -- 8. Climate -- 9. Black Sea -- 10. Inland Waters -- 11. Glaciers -- 12. Soils -- 13. Flora -- 14. Fauna -- 15. Landscapes -- 16. Tourism and Recreation -- 17. Protected Areas and Remarkable Features of Inorganic Nature -- 18. Environment Protection.
Keywords: Physical geography; Geology; Human ecology-Study and teaching; Natural disasters; Physical Geography; Geology; Environmental Studies; Natural Hazards